"Every good learner uses resources": leveraging student interjections to provide scaffolding in a U.S. sheltered english classroom. (2nd October 2021) - Linares, Rebecca E.
ABSTRACT: This paper explores how a monolingual English-speaking teacher working with transnational emergent multilinguals (TEMs) in a sheltered English classroom in the U.S. capitalized on students' interjections turning them into teachable moments. Specifically, it explores how these instances allowed the teacher to model and teach TEMs how to draw on existing skills and resources when they encounter a challenge. Drawing on observational and artefact data gathered during social studies lessons on U.S. symbols, this paper highlights how the teacher leveraged student interjections to scaffold students' understanding of how to (1) utilize classroom resources, (2) leverage existing linguistic knowledge, and (3) access background knowledge. This paper suggests that the teacher's response to students' interjections sought to support them in developing the skills needed to engage in self-scaffolding by accessing and utilizing available resources. Monolingual teachers often feel unprepared when encountering TEMs; however, this paper suggests that if they adapt practices that are already part of their pedagogical practice and maintain an open stance toward students' diverse ways of participating, all stakeholders will benefit.